Treaty Handbook - Nations Unies (United Nations, 2012)
Revised and updated, this handbook by the Treaty Section of the United Nations Office of Legal Affairs is intended as a contribution to UN efforts to assist States in becoming parties to the international treaty framework. It is written in simple language and, with the aid of diagrams and step-by-step instructions, touches upon many aspects of treaty law and practice. This handbook is designed for use by States, international organizations and other relevant entities. In particular, it is intended to provide some degree of assistance to States that may have scarce resources and limited technical proficiency in treaty law and practice to participate fully in the multilateral treaty framework.